Stitch by stitch: knitting as ornamentation, form and formwork - Sahlin, Karin Elisabeth (My University, 2023)
A big shift in the building industry must be made due to climate change. Doubly curved geometry in architecture are often a result of structural optimization, and can be made with material efficient constructions of reinforced concrete. These geometries could therefore be used to decrease the building industry’s impact on the environment. Unfortunately, they are both expensive and often built with material intensive structural solutions. KnitCrete is a formwork system which has the potential of drastically reduce the amount of concrete and single-used formwork material. By tensioning knitted textile against a supporting falsework, it can be used as a stay-in-place mold for casting. This thesis investigate fiber in architecture through the principles of KnitCrete. It explores the design possibilities of the method with an aim to understand how knitting, form and ornamentation can interact in an architectural design. The focus lies in how the knitting’s inherent properties and attributes can be used as a design tool when using the KnitCrete method. The possibilities and limitations with knitting is the core and framework for this thesis. The explorations are divided in two parts. The first part is investigating the potential of ornamentation in a knitted structure and the second part explores the possibilities of creating form with the knitted fabric. This form searching resulted in various models. Through hands on explorations, I have showed that the color of yarn and coating, how the knitting is tensioned, size of the cavities, choice of knitting pattern and where you choose to place increases and decreases determine how the final visual expression will be. Lace knitting patterns have been of special interest since they are created by alternating smaller and bigger cavities. These patterns not only create an ornamentation, but also gives the surface a varying texture when coated. In order to approach KnitCrete in practice, the explorations were combined in to a pavilion. In this work, the complexity of creating a knitting pattern from a large bespoke, doubly-curved geometry become evident. This process must be simpler if KnitCrete is to be used as an effective construction technique in the future.
Keywords: KnitCrete; Doubly-curved geometry; Lace knitting pattern